Listening service to the elderly: Considerations on an extension project in the context of the pandemic - Marcolino-Galli, Juliana; Suzuki Kemmelmeier, Veronica; Magni, Cristiana; Pereira Prado, Débora Cristina; Musial, Denis Cezar (Guará Journal, 2022)
The elderly population suffered the greatest impacts in the coronavirus pandemic, as it was the group with the highest le-thality. This article presents the results of the extension project “Service to listen to the elderly in social isolation in the context of the pandemic”, in partnership with the Secretary of Social As-sistance. We present the implementation of a listening service carried out by telephone calls for elderly people in situations of vulnerability, the profile served and a reflection on the extensionist action in times of mourning. We highlight an extension action that was adapted to the context of social isolation.